The psychological impact of the COVID-19 pandemic on physiotherapists in Sri Lanka: a cross-sectional online-based study - Samarakoon, Jithmi N.; Wettasinghe, Asha H. (International Journal Of Community Medicine And Public Health, 2022)
Background: The COVID-19 pandemic is currently a severe challenge for healthcare workers, with significant implications for their mental health. Physiotherapy is one of the healthcare professions on the frontline managing this pandemic and is directly exposed to the virus. The aim of the study was to determine the impact of this pandemic on the psychological health of physiotherapists in Sri Lanka. Methods: A descriptive cross-sectional study was conducted among physiotherapists who were recruited from government and private hospitals via purposive sampling. Depression-anxiety-stress scale-21 was used to assess psychological health and was distributed online. Results: The sample comprised 48 participants (males=33.3%; females=66.7%; age=30.2±3.8 years). The rates with extremely severe, severe, moderate and mild stress were 4.8%, 33.3%, 35.7% and 16.7% respectively and 9.5% of them had no stress perceived. No physiotherapists were found in normal or mild anxiety and depression categories. Moderate, severe and extremely severe anxiety levels were found in 9.5%, 28.6% and 61.9% of physiotherapists respectively. There were 28.6% physiotherapists with extremely severe depression, 19.0% with severe depression and 52.4% with moderate depression. There was a positive correlation and a significant association of stress with depression (r=0.876, p<0.001), stress with anxiety (r=0.780, p<0.001) and anxiety with depression (r=0.752, p<0.001). Stress, anxiety and depression had no significant associations with age and gender (p>0.05). Fear of infecting family members was found as the main cause of stress (81%). Conclusions: Physiotherapists had elevated levels of anxiety, depression, and stress, highlighting the significance of systematically monitoring physiotherapists’ mental health and implementing supportive measures to improve their well-being during the crisis.